Hierarchies from landscape probability gradients and critical boundaries - Oleksii Matsedonskyi (Journal of High Energy Physics)
Abstract If the gradient of a probability distribution on a landscape of vacua aligns with the variation of some fundamental parameter, the parameter may be likely to take some non-generic value. Such non-generic values can be associated to critical boundaries, where qualitative changes of the landscape properties happen, or an anthropic bound is located. Assuming the standard volume-weighted and the local probability measures, we discuss ordered landscapes which can produce several types of the aligned probability gradients. The resulting values of the gradients are defined by the “closeness” of a given vacuum to the highest- or the lowest-energy vacuum. Using these ingredients we construct a landscape scanning independently the Higgs mass and the cosmological constant (CC). The probability gradient pushes the Higgs mass to its observed value, where a structural change of the landscape takes place, while the CC is chosen anthropically.